THE USE OF MOLECULAR MARKERS METALOTHIONEIN PROTEIN FOR MONITORING MARINE POLLUTION DUE TO HEAVY METALS MERCURY IN Apogon beauforti IN AMBON BAY - Dominggus Rumahlatu; Fredy Leiwakabessy (Diponegoro University, 2016)
The heavy metal Hg is a global issue because it is toxic to living organisms. Therefore, monitoring levels of Hg in Ambon Bay is important to do. This is a study about monitoring the levels of heavy metals Hg in the waters of Ambon Bay in 2013 and 2014 by using Apogon beauforti as bio-indicators and Metalothionein-1 (MT-1) as a biomarker to determine the accumulation of Hg in relation to the concentration and expression of MT-1 in the tissue of A. beauforti. The samples used were 50 fish of A. beauforti taken at four different stations with purposive sampling procedure. The analysis of Hg content used AAS method, the expression of MT-1 was determined by western blotting method, and MT-1 concentrations were determined by using ELISA method in the laboratory of Brawijaya University. On the average, the results of the analysis of Hg content indicated that the accumulation of heavy metal Hg varied in four different stations. The levels of Hg in the tissue of A. beauforti in 2014 at station 1 increased, while the levels of Hg at stations 2, 3, and 4 decreased. However, the calculation results of MT-1 concentration by ELISA showed an increase in the concentration of MT-1 in 2014 compared to that in 2013. This result was supported with the fact that the protein tape expressed on the test results of western blotting was very thick. It indicated that the longer the organism exposed to heavy metals Hg, the more increased the accumulation of Hg. Thus, the expression and the concentration of MT-1 would also increase.